The Gravity Model of Indonesian Bilateral Trade - setyo tri wahyudi; Riyandi Saras Anggita (Institute of Research and Community Service, University of Brawijaya)
This study aims to examine the trade of Indonesia with 10 top export partner using the gravity model of trade. The panel regression analysis with fixed effect model was conducted in order to acknowledge the relationship among the variables Constant Gross Domestic Product, Per Capita Gross Domestic Product, transportation cost, and Real Effective Exchange Rate on export of Indonesia with 10 partners. This study using secondary data with panel regression analysis and research instruments were tested using chow test, hausman test and classical assumption test. The panel regression result showed that simultaneously and partially Constant Gross Domestic Product, Per Capita Gross Domestic Product, transportation cost and Real Effective Exchange Rate had significant effect on export of Indonesia.